Effectiveness of telemedicine in response to the COVID-19 pandemic - Souza,Maria Angela de (2021)
SUMMARY OBJECTIVE: The aim of this study was to evaluate the utility of the telemedicine care model implemented to treat and guide patients with COVID-19 related symptoms and indicators during the pandemic. METHODS: This is a retrospective study with data collected from the electronic records of standardized forms for assistance. As a way of evaluating the work performed, the number of consultations, types of referrals, efficiency of care, and patient satisfaction were observed. RESULTS: Between April 2 and October 15, 2020, 92 professionals attended 3,660 patients by telemedicine; out of them, 523 (14.3%) were referred to a COVID-19 attending room, 128 (3.5%) to other specialties, 123 (3.4%) to a general emergency department, and 2,886 (78.9%) were monitored via home care. Of the total number of patients, 81 (2.2%) were hospitalized, and 13 (0.35%) died. CONCLUSION: Telemedicine offered useful tools for the care, treatment, and monitoring of patients with COVID-19 during the pandemic. The service was considered by most respondents as satisfactory, resolutive, or safe.